Mycotoxin contamination of hazelnut grown in Azerbaijan and aspergillus communities associated with the crop - Aghayev, F.; Bandyopadhyay, R.; Battilani, P.; Ortega-Beltran, A (2025)
In Azerbaijan, hazelnut (Corylus avellana L.) is a crop of economical and nutritional importance. However, recent aflatoxin contamination events in hazelnut produced in Azerbaijan are posing health risks to consumers and reduce marketability. Aflatoxin and fumonisin levels were examined in hazelnuts collected at 33 farmers’ stores, one month after the 2022 harvest under various storage conditions, from two regions in Azerbaijan. All hazelnut samples were contaminated both with aflatoxins (range = 1.1 to 7.2 µg/kg) and fumonisins (range = 0.12 to 0.30 mg/kg). Aspergillus section Flavi fungi were isolated and both aflatoxin producers and atoxigenic (incapable of producing aflatoxins) isolates were identified. Several members of vegetative compatibility group IT006, to which the Italian aflatoxin biocontrol isolate MUCL54911 belongs, were found to be native to Azerbaijan. In laboratory competition assays, MUCL54911 reduced aflatoxin produced by three types of Aspergillus fungi by 97.5 to 100%, which indicates that biocontrol could be an option to reduce aflatoxin in hazelnut. Future research efforts should be geared toward detecting and characterizing additional atoxigenic isolates, optimizing biocontrol application for hazelnut, and implementing agronomic and post-harvest practices to manage aflatoxin throughout the value chain. For effective implementation of integrated mycotoxin strategies, coalitions composed of farmers, research institutions, non-governmental organizations, private sector, and government agencies are needed.